(untitled) (Global Journal of Medical Research, 2018)
Some members of the family Enterobacteriaceae were isolated from Obafemi Awolowo University sewage oxidation pond (target site) and characterize by various biochemical test (citrate test, Gram stain, catalase test, idole production, fermentation of sugar, starch hydrolysis, Nitrate reduction, oxidative-fermentative test, gelatin hydrolysis and Methyl Red Voges-Proskauer test); the antibiotic sensitivity pattern of the isolate were also carried out. All was done under an aseptic condition. The total bacterial count (TBC) obtained from the target site was higher than those obtained from the relative site (1: before the sewage enter) and (2: after leaving) the oxidation pond. The biochemical tests identified the following: Citrobacter diversus, Salmonella arizonae, Typical Salmonella, Escherichia coli and Providencia alcalifaciens, all belonging to the family Enterobacteriaceae. Investigation of the antibiotic sensitivity test revealed that Cefuroxime and Ampicillin were not effective against all the bacteria isolates.